2017
DOI: 10.1038/srep41516
|View full text |Cite
|
Sign up to set email alerts
|

Mx1, OAS1 and OAS2 polymorphisms are associated with the severity of liver disease in HIV/HCV-coinfected patients: A cross-sectional study

Abstract: The mechanisms involved in the chronic hepatitis C progression are incompletely understood. The aim was to analyze the association between 2′5′oligoadenylate synthetase 1,2 and 3 (OAS1-3) and myxovirus resistance proteins 1 (Mx1) polymorphisms and severity of liver disease in human immunodeficiency virus (HIV)/hepatitis C virus (HCV) coinfected patients. We performed a cross-sectional study in 219 patients that underwent a liver biopsy. DNA genotyping for Mx1 (rs469390), OAS1 (rs2285934), OAS2 (rs1293762) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Since the identification of the Flv gene, some human and equine OAS1 alleles have been linked to increased susceptibility to WNV-induced encephalitis (102), demonstrating the importance of Oas1 in the control of WNV infection across multiple species. Alleles of human Oas1 with reduced activity against WNV were also found to have a reduced ability to inhibit HCV replication and are indicators of disease progression in HCV-infected patients (103)(104)(105).…”
Section: Control Of Flavivirus Infection By Oas1bmentioning
confidence: 99%
“…Since the identification of the Flv gene, some human and equine OAS1 alleles have been linked to increased susceptibility to WNV-induced encephalitis (102), demonstrating the importance of Oas1 in the control of WNV infection across multiple species. Alleles of human Oas1 with reduced activity against WNV were also found to have a reduced ability to inhibit HCV replication and are indicators of disease progression in HCV-infected patients (103)(104)(105).…”
Section: Control Of Flavivirus Infection By Oas1bmentioning
confidence: 99%
“…Previous research has also identified history of imprisonment as one of the major risk factors for HCV infection in Iran and around the world (15,16,33,34). Many PWID with a history of imprisonment have poor health.…”
Section: Variables Correlated With Hcvmentioning
confidence: 99%
“…The prevalence of HCV infection in PWID ranges from 20% to 90% in different studies (5,(9)(10)(11)(12)(13)(14)(15)(16)(17). High-risk injection behaviors are the leading cause of HCV infection among PWID (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, OAS1 was found to have the most links with other nodes in the glomerular PIN. Early studies have shown that OAS1 is associated with hepatitis C virus infection, multiple sclerosis, and type 1 diabetes [29-31]. However, the relationship between OAS1 and CKD remains to be established.…”
Section: Discussionmentioning
confidence: 99%